1994
DOI: 10.1108/03090599410068024
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education and Training Programmes:

Abstract: Reviews literature highlighting a number of problems associated with entrepreneurship education and training programmes. The major problem relates to balance: too much of an emphasis on knowledge and not enough on competence; too much emphasis on information transfer learning methods and not enough on individual small group learning methods such as project teams, peer exchange, individual counselling and workshops. There is very little evaluation of the effectiveness of such programmes. There is a lack of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
294
1
25

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(324 citation statements)
references
References 12 publications
4
294
1
25
Order By: Relevance
“…There are also a great deal of reports, syntheses and evaluations of educational experiments in the field of university entrepreneurial training (Garavan and O'Cinneide 1994;Gorman et al 1997). It is remarkable that the reported experiments mainly concern management training at a university level, even though an awareness of entrepreneurial attitudes involving initiative-taking and an approach to changes can, and should be addressed very early (Neunreuther, 1979).…”
Section: The Influence Of Trainingmentioning
confidence: 99%
“…There are also a great deal of reports, syntheses and evaluations of educational experiments in the field of university entrepreneurial training (Garavan and O'Cinneide 1994;Gorman et al 1997). It is remarkable that the reported experiments mainly concern management training at a university level, even though an awareness of entrepreneurial attitudes involving initiative-taking and an approach to changes can, and should be addressed very early (Neunreuther, 1979).…”
Section: The Influence Of Trainingmentioning
confidence: 99%
“…However, evaluations of such programmes cast uncertainties on their effectiveness (Garavan and O'Cinneide, 1994). Gibb (1997) considered the impact of traditional training and development on small firms, recognising two types of learning -adaptive learning in order to cope with change and generative learning involving creative thinking.…”
Section: Entrepreneurial Personality and Learningmentioning
confidence: 99%
“…The decisions on teaching methodologies in entrepreneurship courses therefore, could be influenced by the aim of the educational objective. Thus, the major challenge of entrepreneurship in relation to education is the appropriateness of curriculum and teaching methods in developing students' entrepreneurial competencies and skills (Garavan & O'Cinneide, 1994). With regard to the content of the entrepreneurial courses, Brown (1999) indicated that the entrepreneurship course content should be informal with an emphasis more on hands-on teaching methods.…”
Section: The Entrepreneurial Curriculum and Contentmentioning
confidence: 99%
“…Responding to this need, many colleges and universities around the world have significantly increased their offerings of entrepreneurship courses over the past 25 years (Fayolle & Klandt, 2006). Entrepreneurship courses are not only offered by Business Institutes, but other Faculties like Social Sciences, Engineering, and Information Technology are also offering these courses in their syllabus (Garavan & O'Cinneide, 1994).The rapid growth of entrepreneurship education in academics is evidence of the fact that female students' participation in entrepreneurial courses has more intentions towards new venture creation than those students who do not participate in entrepreneurship education. Formal entrepreneurial education has an impact on female students' inclination towards entrepreneurship as a career option (Hansemark, 1998).…”
Section: Introductionmentioning
confidence: 99%